Methods for Dispersion of Carbon Nanotubes in Water and Common Solvents. Issue 1700 (2014) - Kharisov, Boris I.; Kharissova, Oxana V.; Méndez, Ubaldo Ortiz
ABSTRACT: Contemporary methods for dispersion of carbon nanotubes in water and non-aqueous media are discussed. Main attention is paid to ultrasonic, plasma techniques and other physical techniques, as well as to the use of surfactants, functionalizing and debundling agents of distinct nature (elemental substances, metal and organic salts, mineral and organic acids, oxides, inorganic and organic peroxides, organic sulfonates, polymers, dyes, natural products, biomolecules, and coordination compounds).